Body self-image disturbances in women with prolactinoma - Pereira,Helen S. (2020)
Objective: To evaluate body dissatisfaction and distorted body self-image in women with prolactinoma. Methods: Body dissatisfaction and distorted body self-image were evaluated in 80 women with prolactinoma. All patients were in menacme, 34% had normal body mass index (BMI), and 66% were overweight. Most patients (56.2%) had normal prolactin (PRL) levels and no hyperprolactinemia symptoms (52.5%). The Body Shape Questionnaire (BSQ) was used to assess the patients’ dissatisfaction with and concern about their physical form, and the Stunkard Figure Rating Scale (FRS) was used to assess body dissatisfaction and distorted body self-image. The patients were divided according to PRL level (normal vs. elevated) and the presence or absence of prolactinoma symptoms. Results: The normal and elevated PRL groups had similar incidences of body dissatisfaction and distorted body self-image. However, symptomatic patients reported a higher incidence of dissatisfaction than asymptomatic patients. Distorted body self-image was less common among symptomatic patients. Conclusion: Symptomatic patients showed higher body dissatisfaction, but lower body self-image distortion. The presence of symptoms may have been responsible for increased body awareness. The perception of body shape could have triggered feelings of dissatisfaction compared to an ideal lean body. Therefore, a distorted body self-image might not necessarily result in body dissatisfaction in women with prolactinomas.